# Math

How to expand, then evaluate, and simplify this log question:

logbase7 (49( 3sqrt x^5))

I put the brackets in myself, I there were originally no brackets nor spaces in the question

1. 👍 0
2. 👎 0
3. 👁 38
asked by Kun
1. log7 49(3√(x^5) )
= log749 + log73 + log7 x^(5/2)
= 2 + log7 3 + (5/2)log7 x

it can't be evaluated unless you give me a value for x

1. 👍 0
2. 👎 0
posted by Reiny

## Similar Questions

1. ### Math

How to expand, then evaluate, and simplify this log question: logbase7 (49( 3sqrt x^5)) I put the brackets in myself, I there were originally no brackets nor spaces in the question

asked by Kun on May 27, 2014
2. ### logarithms

evaluate each log. Ln e^3 logbase(1/1000) expand each log. logbase5 radical41/43 logbase7 8xy^4/3z^3 logbase5 4(7radicalxy^z)

asked by help! on May 2, 2010
3. ### math(Please help)

1) use the properties of logarithms to simplify the logarithmic expression. log base 10 (9/300) log - log 300 log 9 = 2 log 3 log 300 = log 3 + log 100 = log 3+2 I just do not know how to put these together now!

asked by Hannah on February 10, 2010
4. ### algebra 2 logaithms

Use the properties of logarithms to evaluate/simplify the expression. 1. 5^log(7x) 2. 10^x + 2 log(x)=x+2 or log(x)=x-2 ????

asked by Anonymous on July 15, 2011
5. ### math -- log and exp. functions

1. evaluate log(base2)[(1/32) X 4^-9] 2. simplify: log x^2 y - (1/2)logx + 3 log y

asked by anonymous on September 22, 2007
6. ### Pre-Cal(Urgent)

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
7. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
8. ### Math(Please check)

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 30, 2010
9. ### Pre-Cal

Find f X g , g X f , and f X f f(x) = 3sqrt x-1 g(x) = x^3 + 1 For f(x) the 3 is little above the sqrt sign. My answers were: f(g(x)) = 3sqrt x^3 + 1 -1 g(f(x)) = 3sqrt (x-1)^3 -1 f(f) = 3sqrt x-1-1 My teacher said these were

asked by Hannah on March 29, 2010
10. ### logarithm functions

use the properties of logarithms to expand the expression as sum, difference or multiple of logarithms. Simplify. a.log(x^3/2) b.log base4 16a

asked by charlie on September 11, 2016

More Similar Questions